(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
Greek and Latin, two of the oldest languages in the world, have made significant contributions to medicine. This comparative study aims to examine the origins and meanings of Greco-Latin terms commonly used in medicine. The article discusses how these languages have influenced the development of medical terminology and how they continue to play an important role in modern medicine.